2011
DOI: 10.1038/emboj.2011.98
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of chromatin binding and nucleosome spacing activity of the nucleosome remodelling ATPase ISWI

Abstract: The evolutionarily conserved ATP-dependent nucleosome remodelling factor ISWI can space nucleosomes affecting a variety of nuclear processes. In Drosophila, loss of ISWI leads to global transcriptional defects and to dramatic alterations in higher-order chromatin structure, especially on the male X chromosome. In order to understand if chromatin condensation and gene expression defects, observed in ISWI mutants, are directly correlated with ISWI nucleosome spacing activity, we conducted a genome-wide survey of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 35 publications
7
55
1
Order By: Relevance
“…Similar approaches performed on ISWI family members in flies and Saccharomyces cerevisiae have documented subtle changes at the TSS or TTS (41)(42)(43) or more dramatic and dispersed effects across the genome (44). From our experiments, we observed that most changes in nucleosome occupancy occurred at an NFR located Ͼ1 kb away from a TSS or TTS.…”
Section: Discussionmentioning
confidence: 51%
“…Similar approaches performed on ISWI family members in flies and Saccharomyces cerevisiae have documented subtle changes at the TSS or TTS (41)(42)(43) or more dramatic and dispersed effects across the genome (44). From our experiments, we observed that most changes in nucleosome occupancy occurred at an NFR located Ͼ1 kb away from a TSS or TTS.…”
Section: Discussionmentioning
confidence: 51%
“…In vivo, ACF and CHRAC behave as assembly factors, promoting the formation of chromatin, particularly repressive chromatin states. Nevertheless, high-resolution mapping of nucleosomes in Iswi mutant males and females indicates that the chromosome condensation defects that they show, especially of the X chromosome in males, are not correlated with global ISWI-dependent nucleosome spacing changes (Sala et al 2011). A more convincing explanation is provided by the observation that ISWI facilitates the association of linker histone H1 and that a reduction of the H1 leads to a chromosomal phenotype similar to the one described above for ISWI loss of function (Siriaco et al 2009).…”
Section: Influence Of Global Chromatin Factorsmentioning
confidence: 85%
“…For example, Isw2, an ISWI homolog in yeast, was found to bind transiently on chromatin and to scan the genome for its targets (Gelbart et al, 2005). Also, Drosophila ISWI appears to bind genes near their promoters, causing specific alterations in nucleosome positioning at the transcription start site (Sala et al, 2011). This premise may be transposed to insulator function as well, i.e.…”
Section: Research Articlementioning
confidence: 99%